Analysis of Extracurricular Adolescent Red Cross Implementation Supporting Factors for Strengthening Student Civic Responsibility - Rohmat Deni Alfauzi; Achmad Muthali'in (Paedagogia: Jurnal Pendidikan, 2023)
This study aims to determine the supporting factors for the implementation of extracurricular PMR in strengthening student civic responsibility at SMAN 2 Sukoharjo. This study was conducted for 5 months using a qualitative descriptive method, namely by emphasizing facts in the field and giving a clear picture. Data collection using observation, interview, and documentation techniques. Data analysis was collected during and after data collection, namely including data reduction and presentation. The results of this study are factors that support the implementation of extracurricular PMR in strengthening civic responsibility in students with school support, involvement of teachers and coaches in PMR activities, qualified trainers and coaches, and resources. This is a supporter of PMR extracurricular activities in strengthening civic responsibility for students at SMAN 2 Sukoharjo.